Hubungan Tuntutan Kuantitatif Pekerjaan dan Konflik Pekerjaan Kehidupan dengan Tingkat Distres Kerja pada Pegawai Rumah Sakit - Yuda Nugraha; Hendra Djamalus (Universitas Faletehan, 2025)
Health care workers are at high risk of experiencing work-related distress both somatic and cognitive due to high quantitative job demands and work–life conflict. This study aimed to determine the relationship between quantitative job demands and work-life conflict with the level of work-related distress among hospital employees. This study used a cross-sectional study design. A total of 279 respondents were involved in the study through total sampling. Data were collected from April to June 2025 using the standardized questionnaire of the long version of the Copenhagen Psychosocial Questionnaire (COPSOQ III). Data analysis was carried out using the Spearman rank correlation test with a significance level of 5% (α = 0.05). The analysis result revealed a positive association between quantitative job demands and somatic distress (ρ = 0.35, p < 0.001) as well as cognitive distress (ρ = 0.42, p < 0.001). Work–life conflict also correlated positively with somatic (ρ = 0.44, p < 0.001) and cognitive distress (ρ = 0.41, p < 0.001). These findings indicate that the greater quantitative job demands and work–life conflicts are associated with higher levels of work-related distress among healthcare workers in hospital.